ANALISIS FRAMING NILAI SIRI’ PADA SOSOK ZAINUDDIN DALAM NOVEL TENGGELAMNYA KAPAL VAN DER WIJCK - muhammad munawir pohan (Universitas Islam Negeri Sumatera Utara Medan, 2018)
The purpose of this research is: (1) to find out how he was reconstructing the value series ' in the novel the sinking Van Der Wijck, (2) to find out to what extent he was representing the value of the series ' at the figure Zainuddin in the novel the sinking Van Der Wijck. This research was conducted with the object of research of novel the sinking Van Der Wijck. Type a descriptive qualitative study was shaped by using analytical techniques framing model Gamson and Modigliani.Data Primer diperoleh dari sumber data utama berupa dialog dan narasi yang menggambarkan budaya siri’ dalam novel tersebut. Data sekunder diperoleh dari bahan bacaan berupa jurnal-jurnal, buku, artikel di internet, dan berbagai hasil penelitian terkait. The results showed that the viewpoints and background strongly influenced someone in interpreting social reality based on construction respectively. In the novel the sinking Van Der Wijck, Hamka was repackaged as the figure Zainuddin characters bleed Makassar-Minang based on the way up. He was quite familiar with the meaning of the series ' major Makassar community but the value of the series ' imagery on Zainuddin still weak. This must not be removed from the background of the Minangkabau people as Hamka (non-Makassar), then there is no great awareness to describe the character of the people of Makassar accordingly on the figure Zainuddin. Similarly, a character in the story of Zainuddin positioned as someone who bleeds Makassar-Minang, outwardly it could just be the blood of Minang rub off on Zainuddin, so not entirely it is capable of holding a sturdy custom Makassar.Keywords: Framing, Siri ', Novel